KEYS TO FINANCIAL PLANNING: EFFECTS OF FINANCIAL LITERACY DURING COVID-19 - Yulfiswandi Yulfiswandi; Justyanita Justyanita; Sephia Septiana; Estina Sativa; Muhammad Saprudin (Universitas Islam Lamongan, 2022)
This study determines the role of financial planning in the Covid-19 era and the influence of financial literacy, financial knowledge, social demographics, and lifestyle during the Covid-19 pandemic. The research method used in this research is a conceptual paper with a literature review approach. The role of variables has a tremendous influence on financial planning where with this knowledge, it is possible to awaken individuals to behave well in financial matters. Covid-19 has a positive impact on financial planning because it can increase awareness of the importance of financial planning to make wise decisions and not behave consumptively. The better a person's behavior in managing his financial planning, the better his financial planning in the future.